If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 8 + -1(4x + 6) = 0.5(5 + -7x) Reorder the terms: 8 + -1(6 + 4x) = 0.5(5 + -7x) 8 + (6 * -1 + 4x * -1) = 0.5(5 + -7x) 8 + (-6 + -4x) = 0.5(5 + -7x) Combine like terms: 8 + -6 = 2 2 + -4x = 0.5(5 + -7x) 2 + -4x = (5 * 0.5 + -7x * 0.5) 2 + -4x = (2.5 + -3.5x) Solving 2 + -4x = 2.5 + -3.5x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '3.5x' to each side of the equation. 2 + -4x + 3.5x = 2.5 + -3.5x + 3.5x Combine like terms: -4x + 3.5x = -0.5x 2 + -0.5x = 2.5 + -3.5x + 3.5x Combine like terms: -3.5x + 3.5x = 0.0 2 + -0.5x = 2.5 + 0.0 2 + -0.5x = 2.5 Add '-2' to each side of the equation. 2 + -2 + -0.5x = 2.5 + -2 Combine like terms: 2 + -2 = 0 0 + -0.5x = 2.5 + -2 -0.5x = 2.5 + -2 Combine like terms: 2.5 + -2 = 0.5 -0.5x = 0.5 Divide each side by '-0.5'. x = -1 Simplifying x = -1
| (5u+4)(7+u)=0 | | 14x(-3x+5)=3 | | x*2+y=36 | | 14x(3x-5)=82 | | 9w^6+24w^5+16w^4=0 | | 3(3z+4)-4(2z-3)=8 | | 4y^4+18y^3-10y^2=0 | | 7z^2-20z-3=0 | | (3x)2-10= | | -18-12/-18+12= | | 8z-4(z-5)+4=4z-16 | | -15-(-4)-7= | | 8z-4(z-5)+4= | | (61000-x)/21350 | | 4x-3(3x-1)+12=15(x+9) | | -4(3-10)= | | -5+(-16)+9= | | 7n^2+14n+5=0 | | r=exp(0.09)-1 | | 20-11=3(x-3) | | 50+5y-17=17y-12-3y | | 36/-4= | | y=1x+16 | | 5h^3-30h^2+40h=0 | | 5(32)= | | -3/4p=18 | | 7-(3n-1)=4-4n | | 7/12-8/3x-5/83/8 | | 60=3x-3 | | +(-2)+5-(-2)= | | 3(3n-5)=(7n+5)+1 | | 5-3(t+3)=-1+2(t-3) |